Pelaksanaan Perjanjian Waralaba pada Cbezt Fried Chicken Ungasan - Ketut Bagus Kurniawan Wahyu Wibawa; Ni Komang Arini Stywati; I Nyoman Sukandia (Fakultas Hukum, Universitas Warmadewa, 2022)
A franchise agreement is an agreement between the franchisor and the franchisee to run a trading business owned by the franchisor according to the equipment installed through the franchisor. In this case, the problem of crime is the non-fulfillment of the rights and responsibilities of the franchisor to the franchise. The formulation of the problem is, how is the Implement of the Franchise Agreement on C'bezt Fried Chicken Ungasan in South Kuta District?2.How is Dispute Settled in the Implement of Franchise Agreements at C'bezt Fried Chicken Ungasan in South Kuta District? The author applies the empirical method. The results of this journal research provide clarification that the parties agree to bind themselves to make a franchise agreement where the party is the giver and recipient of the franchise. In a franchise contract, of course, there are rights and obligations that have been agreed upon in the franchise agreement. Rights and obligations arise as a result of the reciprocal relationship of the parties. Settlement of disputes arising from default on the franchise at C'bezt Fried Chicken Ungasan is carried out through deliberation, and if the deliberation cannot be resolved it will be resolved at the Denpasar District Court.